A Tale of Parallel Processes of Gender (In-)Equality: How Big is the Glass Ceilings for Mena Women? - Ömer Tuğsal Doruk; Francesco Pastore (Global Labor Organization (GLO), 2022)
In all the MENA countries considered in this study, namely Jordan Egypt and Tunisia, there has been a significant decrease in the female labor force participation rate over the last two decades. Moreover, existing analysis and the anecdotal evidence suggest that it may be problematic for women to reach a white collar high skill job, also in the more protected public sector, though there is very little empirical evidence on this. By using repeated cro ss sections of individuals covering periods of up to 20 years (for Egypt), we examine the evolution of the glass ceiling problem for women resorting to the matching approach, which, to our knowledge, has never been used in this field. Instead of looking at the gender gap along the wage distribution, we assess the probability to reach the top professions of manager, professional and technician or associate professional. We find a sizeable glass ceiling effect in all the countries considered. It is a persistent phenomenon across all the industrial sectors and the years considered. The present study sheds new light on the glass ceiling effect for woman in the MENA countries, which is relevant also for other countries
Keywords: J16; J71; K38; O53; P52; 330; Glass ceilings; Woman employment; labor force; Egypt; Jordan; Tunisia